Next Steps for Developing a Precision Medicine Approach to Word Learning After Pediatric Traumatic Brain Injury: A Tutorial and Roadmap for Clinical Research in Speech-Language Pathology - Emily L. Morrow; Melissa C. Duff (American Journal of Speech-Language Pathology, 2026)
Purpose: Following discussions at the 2026 International Cognitive-Communication Disorders Conference, we advocate for increased study of word learning in children with traumatic brain injury (TBI). We provide a conceptual foundation and highlight the potential of word learning as a mechanistic framework linking memory, learning, and academic and long-term rehabilitation outcomes in this population. Method: In this narrative review, we discuss the complexities of the word learning process; how word learning relates to memory, neural, and cognitive development; and the unique opportunities afforded by studying each component and stage. We describe how word learning may underlie functional outcomes in pediatric TBI, making it a promising target for research and rehabilitation. Finally, we explore principles to guide a precision approach to the study and treatment of individual word learning profiles as mechanisms of rehabilitation and academic outcomes for children with TBI. Results and Conclusions: Pediatric TBI is a common and growing health crisis with well-established and long-ranging consequences for academic success. However, there has been limited attention on specific academic skills, such as word learning, and their underlying mechanisms. Such work may hold promise in advancing cognitive, interpersonal, and academic outcomes after childhood TBI. The word learning literature is ripe with established protocols that consider learning as an iterative, dynamic process occurring in daily contexts. Considering the full complexity of word learning in study design allows for assessment of the contributions of multiple cognitive systems and behavioral factors to the learning process. Resultant findings could lead to strides in precision rehabilitation and clinical decision making that support improved memory, learning, and developmental trajectories for children after TBI.